Implicações da teoria histórico-cultural no processo de formação de professores da educação infantil - Magalhães, Cassiana [UNESP] (2014)
This thesis is a result of research on Implications of Historical-Cultural Theory in Teacher Education of Early Childhood Education held in a Child Education Centre of the City of Londrina-PR, with the participation of eight teachers working with 0 to 5- year-old children. It aimed to understand possible changes in pedagogical practice of teachers participating in the research study from the Historical-Cultural Theory, based on the following hypothesis: Education is an objectification of the sphere of non-daily activity, of the complex sphere of human activity. Therefore, it is an activity that requires reflection, intention, theoretical foundation. However, the logic that has guided teaching is the logic of everyday life. The problem of this research is presented as follows: How can we impact the teaching job in humanizing perspective through the Historical-Cultural Theory? To answer the question, data were generated in 2012 with the completion of the weekly group studies in the first semester and biweekly in the second half. Each study generated an individual reflection writing used in the research analysis. Besides the reflections, eighteen observation sessions occurred in classrooms of the participating teachers. Data were analyzed focusing on the following concepts and their embodiments in practices observed: Learning and Development; Education as a Humanization process; The organization of teaching practice. The results indicated that the practice of reading texts which explain Historical-Cultural Theory provides bases to impact the teaching work qualitatively affecting the practices toward a developmental education. These results were shown in the teachers’ conceptions on the concepts of child, school, and teacher, and led to changes in teaching practices in relation to the organization of the space, the place of children in relationships experienced in school, to the child’s place in planning daily activities and to the...